Age- and Sex-Related Differences in Motor Performance During Sustained Maximal Voluntary Contraction of the First Dorsal Interosseous - Sars, Valerie; Prak, Roeland F.; Hortobágyi, Tibor; Zijdewind, Inge (Frontiers in Physiology, 2018)
Age and sex affect the neuromuscular system including performance fatigability. Data on performance fatigability and underlying mechanisms in hand muscles are scarce. Therefore, we determined the effects of age and sex on force decline, and the mechanisms contributing to force decline, during a sustained isometric maximal voluntary contraction (MVC) with the index finger abductor (first dorsal interosseous, FDI). Subjects (n = 51, age range: 19 to 77 years, 25 females) performed brief and a 2-minute sustained MVC with the right FDI. Abduction force and root mean squared electromyographic activity (rms-EMG) were recorded in both hands. Double-pulse stimulation was applied to the ulnar nerve during (superimposed twitch) and after (doublet-force) the brief and sustained MVCs. Compared to females, males were stronger (134%, p <0.001) and exhibited a greater decline in voluntary (difference: 8%, p = 0.010) and evoked (doublet) force (difference: 12%, p = 0.010) during and after the sustained MVC. Age did not affect MVC, force decline and superimposed twitch. The ratio between the doublet- and MVC-force was greater in females (0.33, p = 0.007) and in older (0.38, p = 0.06) individuals than in males (0.30) and younger (0.30) individuals; after the sustained MVC this ratio increased with age and the increase was larger for females compared to males (p = 0.04). The inadvertent contralateral, left force and rms-EMG activity increased over time (2.7 to 13.6% MVC and 5.4 to 17.7% MVC, respectively). Males had higher contralateral forces than females (p = 0.012) and contralateral force was higher at the start of the contralateral contraction in older compared with young subjects (difference: 29%, p = 0.008). In conclusion, our results suggest that the observed sex-differences in performance fatigability were mainly due to differences in peripheral muscle properties. Yet the reduced amount of contralateral activity and the larger difference in evoked versus voluntary force in female subjects indicate that sex-differences in voluntary activation should not be overlooked. These data obtained in neurological healthy adults provides a framework and help the interpretation and referencing of neurophysiological measures in patients suffering from neuromuscular diseases, who often present with symptoms of performance fatigability.